Effect of Intermittent versus Continuous Light Exposure on Pupillary Light Response, As Evaluated by Pupillometry - Ba-Ali, Shakoor; Lund-Andersen, Henrik; Ahmadi, Hamid; Brøndsted, Adam Elias (Frontiers in Neurology, 2018)
Objective: Continuous and intermittent stimuli with green light affect the pupillary light response (PLR) differently. Since the majority of pupillometric studies use blue and red lights, we investigated the effect of continuous and intermittent stimulations on the PLR using red and blue lights. Methods: Seventeen healthy subjects underwent continuous- and intermittent light stimuli, using red (643 nm) and blue light (463 nm). To avoid the influence of pupil size on the amount of light entering the eye, the procedures were repeated with the stimulus-eye in dilated condition. The maximal pupillary constriction and the early re-dilation phase of post-illumination pupillary response (PIPR) represented the mixed response of melanopsin and rod-cone photoreceptors. The late re-dilation PIPR was the marker of melanopsin-containing retinal ganglion cells. Results: Intermittent stimuli with blue light elicited significantly larger maximal contraction during dilated condition (P = 0.001), and larger sustained pupillary contraction under dilated as well as undilated condition (P < 0.001) compared to continuous light exposure. Except the PIPREarly during undilated condition, none of the PIPR metrics were significantly different between intermittent and continuous blue light stimuli. Intermittent red light stimuli elicited also a more sustained pupillary contraction regardless of mydriatic instillation (P ≤ 0.02). In addition, intermittent red light exposure resulted into a slightly larger PIPREarly under undilated condition (P = 0.02), and a slightly larger PIPRLate under dilated condition (P = 0.049). Except the PIPRLate to continuous red light stimulus, all PIPR parameters were larger when the light was presented after induction of unilateral mydriasis. Conclusion: PLR parameters during and after light exposures depend on both the light stimulation mode and the entrance pupillary size.